Epistimologi Pendidikan Prespektif Sekuler dan Islam : Kajian Perbandingan - Sawitri, Riska; Kadar Yusuf; M. Firdaus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the comparative epistemology of education from a secular and Islamic perspective, as well as its implications for the goals and orientation of education. This study uses a qualitative approach with library research methods through analysis of various relevant scientific literature. The results of the study indicate that secular educational epistemology rests on rationalism and empiricism as the primary sources of knowledge, with truth criteria based on scientific verification and academic consensus, and tends to separate the metaphysical dimension from the educational process. Meanwhile, Islamic educational epistemology is integralistic, making revelation, reason, senses, and intuition complementary sources of knowledge within the framework of monotheism. Secular education is oriented towards the formation of rational and materially productive individuals, while Islamic education aims to form a perfect human being who integrates intellectual, moral, and spiritual intelligence. This comparison shows that fundamental differences lie in the philosophical foundations and worldviews of each paradigm. Therefore, efforts are needed to integrate knowledge within the framework of Islamic epistemology so that education can respond to the challenges of modernity without losing its transcendental dimension.